A New Look at an Old Petroleum Province - Gerhard, Lee C. (Current Research in Earth Sciences, 2004)
New petroleum paradigms in mature basins can be derived from re-examining geological parameters without bias of preceding theory. Kansas has a long history of oil and gas production with over 300,000 wells drilled. Precambrian basement faults in Kansas control the development of later structures, and probably, reservoirs. This study and re-interpretation of geologic history has identified a possible new play along reverse and thrust faults of the Humboldt Fault Zone along the eastern margin of the Nemaha uplift. This paper also suggests that the lack of significant petroleum production in the Salina basin is the result of migration barriers created by faults at the junction of two major fracture trends, rather than by limited local generation and migration.